2010
DOI: 10.1111/j.1464-0597.2009.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

Academic Procrastination in Two Settings: Motivation Correlates, Behavioral Patterns, and Negative Impact of Procrastination in Canada and Singapore

Abstract: Two studies are reported examining academic procrastination and motivation in 1,145 university students from Canada and Singapore. In Study 1, relationships between procrastination and motivation variables were found to be similar across contexts, with self-efficacy for self-regulated learning most strongly associated with procrastination in both contexts. In Study 2, patterns of procrastinating behavior and the negative impact of procrastination were examined and compared in Canadian and Singaporean undergrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
69
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 26 publications
14
69
1
2
Order By: Relevance
“…Tuckman and Sexton (1989) suggested that procrastination is the lack of self-regulated performance. Procrastination is associated with a low level of self-efficacy (Howell & Watson, 2007); low levels of resource management strategies such as effort regulation, peer learning, and help seeking (Milgram, Dangour, & Raviv, 1992;Synn, Park, & Seo, 2005); high anxiety (Lay & Silverman, 1996;Milgram & Naaman, 1996;Tice & Baumeister, 1997); and unsatisfactory performance (Klassen et al, 2010).…”
Section: Self-regulated Learning and Procrastinationmentioning
confidence: 99%
“…Tuckman and Sexton (1989) suggested that procrastination is the lack of self-regulated performance. Procrastination is associated with a low level of self-efficacy (Howell & Watson, 2007); low levels of resource management strategies such as effort regulation, peer learning, and help seeking (Milgram, Dangour, & Raviv, 1992;Synn, Park, & Seo, 2005); high anxiety (Lay & Silverman, 1996;Milgram & Naaman, 1996;Tice & Baumeister, 1997); and unsatisfactory performance (Klassen et al, 2010).…”
Section: Self-regulated Learning and Procrastinationmentioning
confidence: 99%
“…The pattern of pacing style means across the three styles in both the faculty (Deadline: M = 2.80, SD = .95; Steady: M = 2.70, SD = .81; U-shaped: M = 3.10, SD = .89) and organisational (Deadline: M = 2.38, SD = .85; Steady: M = 2.94, SD = .83; U-shaped: M = 2.76, SD = .89) samples tended to be less deadline oriented than the student means reported in Tables 2,3,4,and 5. Furthermore, there has been some initial evidence in the literature of cultural differences in deadline avoidant behaviors (Klassen, Ang, Chong, Krawchuk, Huan, Wong, & Yeo, 2010), making cross-cultural differences in pacing style and consequent behaviors an important area for further investigation. Additional research in more diverse contexts should verify the generalisability of findings.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…8, No. 10;2015 On gender, the academic negligence researches, has largely equivocal, different, ambiguous and complex. Some of these studies (e.g., Ferrari et al, 1995;Kagan, 2009;Ozer & Dmyrvfrary, 2009) suggest that males are more lax .However, other studies indicate that there is not significant relationship between gender and negligence (Clark & Hill, 1994;Haykvk, 1993;Solomon & Ruthblum, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…8, No. 10;2015 been found that the negligence involved a motivational problem, as negligence's hardly are raised; Therefore more likely to work in the school and study for exams until the last possible moment, they negligence (Takmn, 1998, quoted by Lee, 2005). Negligence often know exactly what is needed to complete a given task but mostly in excited their motivation to achieve academic goals on given time and fail (Strand, 2011).…”
Section: Introductionmentioning
confidence: 99%